2021
DOI: 10.1186/s12915-021-01167-1
|View full text |Cite|
|
Sign up to set email alerts
|

Telomerase subunit Est2 marks internal sites that are prone to accumulate DNA damage

Abstract: Background The main function of telomerase is at the telomeres but under adverse conditions telomerase can bind to internal regions causing deleterious effects as observed in cancer cells. Results By mapping the global occupancy of the catalytic subunit of telomerase (Est2) in the budding yeast Saccharomyces cerevisiae, we reveal that it binds to multiple guanine-rich genomic loci, which we termed “non-telomeric binding sites” (NTBS). We characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 126 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…To gain insight into factors that may contribute to dnTA, we examined whether putative SiRTAs preferentially overlap with the binding sites of proteins related to telomere addition such as Est2 (a component of telomerase recently shown to associate with internal chromosome sites; Lendvay et al 1996; Pandey et al 2021), Rap1 (a transcription regulator that also binds telomeric repeats and affects telomere length homeostasis; Conrad et al 1990; Rhee & Pugh, 2011), and Pif1 (a helicase that negatively regulates telomerase at telomeres and DNA double-strand breaks; Schulz and Zakian 1994; Paeschke et al 2011). We also examined the correlation between predicted SiRTAs and fragile sites, identified as regions that associate with γH2AX even in the absence of exogenous damage (Downs et al 2000; Capra et al 2010), and between SiRTAs and sequences predicted to form G-quadruplex structures (Capra et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into factors that may contribute to dnTA, we examined whether putative SiRTAs preferentially overlap with the binding sites of proteins related to telomere addition such as Est2 (a component of telomerase recently shown to associate with internal chromosome sites; Lendvay et al 1996; Pandey et al 2021), Rap1 (a transcription regulator that also binds telomeric repeats and affects telomere length homeostasis; Conrad et al 1990; Rhee & Pugh, 2011), and Pif1 (a helicase that negatively regulates telomerase at telomeres and DNA double-strand breaks; Schulz and Zakian 1994; Paeschke et al 2011). We also examined the correlation between predicted SiRTAs and fragile sites, identified as regions that associate with γH2AX even in the absence of exogenous damage (Downs et al 2000; Capra et al 2010), and between SiRTAs and sequences predicted to form G-quadruplex structures (Capra et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Overlap between putative SiRTAs and other genomic annotations was determined using a permutation-based enrichment test. Enrichment for SiRTAs with several different genomic annotations was determined: (1) essential and non-essential genomic regions (Giaever et al 2002); (2) Est2 binding sites (Pandey et al 2021); (3) Pif1 binding sites (Paeschke et al 2011); (4) γH2AX binding sites (Capra et al 2010); (5) G-quadruplex regions (Capra et al 2010) and (6) Rap1 binding sites (Rhee and Pugh 2011). When the original dataset included strand information (as in the case of G4-sites) that information was considered in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To date, few studies have examined ETS2 in tumors, and only a few studies have shown that ETS2 is associated with DNA damage ( 29 , 50 , 51 ). This may be why ETS2 improves the prognosis of tumor patients ( 27 ). CDKN2A , also known as P16 , is currently a very common factor in tumor research, and consistent with our findings, it has been confirmed to be a poor prognostic factor in patients with CRC due to its hypermethylation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have found that increased CDKN2A expression leads to reduced stem cell proliferation, thereby confirming the relationship between CDKN2A expression and stem cell regeneration ( 24 - 26 ). Currently, little research has been conducted on ETS2 in tumors, and some studies have indicated that ETS2 is prone to accumulate DNA damage ( 27 - 29 ); however, in a study by Chen et al ETS2 was found to be a pro-oncogene in CRC ( 30 ). Therefore, further research needs to be conducted to explore whether CDKN2A and ETS2 have potential value in predicting prognosis and immune therapy response.…”
Section: Introductionmentioning
confidence: 99%